Law Enforcers as Offenders: Applying Differential Association Theory to Police Sexual Abuse in Indonesia - Isna Khalimatussa’diah Az-Zahra; Ridwan Arifin; Ngaboawaji Daniel Nte; Varun Chhachhar (Sangia Nibandera Law Research, 2026)
Sexual harassment and abuse are forms of violence rooted in structural gender inequality, shaped not merely by individual desire but by socially constructed norms influencing both perpetrators and victims. In many cases, victims are unjustly blamed, reflecting cultural attitudes that normalize or trivialize sexual misconduct. This study examines police-perpetrated sexual abuse in Indonesia, highlighting the paradox of law enforcers acting as offenders. Such cases have drawn significant public attention, raising concerns about ethical violations and deviant behavior within law enforcement institutions. This research aims to analyze the phenomenon from both legal and criminological perspectives, applying Differential Association Theory as proposed by Edwin H. Sutherland. The theory explains that deviant behavior is learned through social interaction within environments that justify or tolerate wrongdoing. This study adopts a qualitative method with a normative-empirical approach, utilizing document analysis, legal frameworks on sexual offenses, and literature on deviance within police institutions. The findings reveal that weak internal supervision, hierarchical power structures, and institutional subcultures contribute to the emergence and persistence of abusive behavior. These conditions enable the internalization of values that justify misconduct, reinforced by peer influence and organizational silence. Furthermore, legal processes in such cases do not always fully reflect principles of justice and public accountability. This study underscores the need for comprehensive institutional reform, including strengthened oversight, ethical training, and transparent accountability systems to prevent future violations and restore public trust.